English Language Teachers’ Perceptions and Challenges in Using Artificial Intelligence in Improving Students’ Critical Thinking Skills - Shara Joy Constantinopla; Judy Anne P. Almendral (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2026)
Artificial intelligence (AI) has demonstrated considerable potential in enhancing students’ critical thinking skills in English language education. Guided by the Technological Pedagogical Content Knowledge (TPACK) framework and supported by the Technology Acceptance Model (TAM), this study employed a descriptive qualitative design to examine English language teachers’ perceptions and challenges in integrating AI into instruction. Fifteen (15) English language teachers from Saniel Cruz National High School were purposively selected. Data were collected through in-depth interviews and reflective journals and analyzed using thematic analysis. Findings revealed that AI supports instructional efficiency while promoting student autonomy, reflective thinking, and engagement. Teachers reported that AI tools facilitate feedback, encourage analytical reasoning, and enhance participation in learning activities. However, challenges such as over-reliance on AI, concerns about accuracy and bias, limited access to resources, and issues related to academic integrity were also identified. The study concludes that AI should be utilized as a supportive pedagogical tool rather than a substitute for human instruction. Effective integration requires ethical awareness, digital competence, and guided implementation to ensure that AI enhances rather than diminishes students’ critical thinking skills.